Optimalisasi Potensi Alam, Ekonomi, dan Budaya Desa Wisata Pupus melalui Pendekatan Green Digital Management - Yitno Purwoko; Erna Wigati; Aceng Gima Sugiama; Tuti Panghastuti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Pupus Tourism Village in Ponorogo Regency is a pioneering tourist village endowed with diverse natural, economic, and cultural potential, yet its development remains constrained by limited infrastructure and insufficient utilization of digital technology. This condition has hindered the optimization of local attractions such as Mloko Sewu, Selorejo Waterfall, Mount Tapak Bimo trekking, as well as local products including palm sugar, coffee, porang, and goat milk in supporting the village economy. This study aims to analyze strategies for optimizing village potential through the application of Green Digital Management (GDM) as an effort to establish sustainable tourism business practices. A qualitative research approach was employed, with data collected through observation, interviews, and documentation. The findings reveal that the implementation of GDM can serve as a strategic approach for Pupus Tourism Village by integrating environmentally based digital promotion, strengthening eco-friendly creative economy initiatives, and revitalizing local culture such as the bersih desa ritual and communal work (gotong royong). The implications highlight the importance of collaboration between government, community, and tourism stakeholders in applying GDM to enhance the competitiveness of Pupus Tourism Village while simultaneously promoting sustainable economic, social, and ecological development.